Korelasi Kurikulum terhadap Hasil Belajar Siswa SMK di Indonesia: Studi Meta Analisis - Prasetyo, Aditya; Iskandar, Ranu; Naryanto, Rizqi Fitri (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to analyze the correlation between curriculum implementation and learning outcomes of Vocational High School (SMK) students in Indonesia through a meta-analysis approach. Meta-analysis was conducted on 50 relevant studies obtained from various National Journals using keywords, such as "Independent Curriculum", "2013 Curriculum", and "SMK Student Learning Outcomes". Data analysis was conducted using JASP software to calculate effect size and standard error. The results of the analysis showed a significant positive correlation between curriculum implementation and SMK student learning outcomes with an average correlation coefficient (rRE) of 0.810 which is classified as high. However, further analysis based on field of expertise and type of curriculum did not show statistically significant differences. Heterogeneity analysis revealed high variability between studies (I² = 88.66%). However, based on the funnel plot and regression tests, there was no strong indication of publication bias. This finding confirms the importance of the role of the curriculum in improving SMK student learning outcomes. Therefore, it is advisable to conduct further exploration of other variables that have the potential to influence student learning achievement.